Political violence and economic development in Latin America : issues and evidence - Solimano, Andrés (CEPAL SantiagoCL, 2004)
Discusses the main economic and political determinants of conflict and terrorism as two main types of political violence. Reviews recent literature on the relation between the process of economic development and conflict and terrorism. Provides empirical evidence on the incidence and nature of these phenomena in the Latin American region in the second half of the 20th century and early 21st century. Discusses how to deal with political violence from an institutional and developmental perspective, including also the prevention of and insurance against conflict and terrorism.